Artificial intelligence-assisted phenotypic monitoring and diagnostic of wastewater microbiome management towards sustainability - Zijian Wang; Yuan Yan; IL Han; Jangho Lee; Guangyu Li; Peisheng He; Annalisa Onnis-Hayden; Nicholas B. Tooker; Zijun Meng; Mark Wallace Miller; Kester McCullough; Stephanie Klaus; et al. (Water Research, 2026)

Geomorphic thresholds regulating Holocene wetland evolution: Multi-proxy evidence from the Upo Wetland, Korea - Jin Young Lee; Sang Deuk Lee; Ho Il Lee; Hyun Ho Yoon; Min Han (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Physics-aware POD–transformer surrogate modeling for building-resolved urban wind prediction using multi-GPU large-eddy simulations - Mingyu Yang; Jungwoo Kim; Jung Min Han; Jung-Il Choi (Building and Environment, 2026)

Antimicrobial and antioxidant activities of Methylobacterium phyllosphaerae KS50439 isolated from Antarctic seawater - Bo Young Byun; Jin A Kim; Jaewon Kim; Jin-Hyoung Kim; Joung Han Yim; Il-Chan Kim; Se Jong Han (Archives of Microbiology, 2026)

A method for identifying revisions in ship drawings using change detection and synthetic revision generation - In-Su Han; Myung-Il Roh; Min-Chul Kong; Seong-Won Choi; Hwasup Jang; Yeonhwa Jo; Gapheon Lee (Ocean Engineering, 2026)

Stage-dependent shifts in bacterial communities and nitrogen cycling during Pyropia cultivation on the west coast of Korea - Hyo-Ryeon Kim; Ju-Hyoung Kim; Seo-Young Kim; Mi-Jeong Han; Il-Nam Kim (Marine Environmental Research, 2026)

Diagnosis classification in EMR data using latent representations and SNOMED-CT mapping for improved medical data integration - Sungsu Oh; In Ho Han; Jae Il Lee; Byung Kwan Choi; Hyunsu Lee (Medical & Biological Engineering & Computing, 2026)

Hydrodynamic interaction between a free surface water wave and a bottom-fixed body near a vertical breakwater by using BEM with a novel Neumann-to-Dirichlet boundary condition - Un-Ryong Rim; Chang-Bom Jong; Song-Hyok Han; Tong-Ju Ho; Yong-Il Jong; Ju-Song Kim; Ryong-Chol Kim; Guk-Chol Ma; Sok-Yun Kim; Hyong-Ju Yang (Wave Motion, 2026)

Mechanistic insights and design optimization of microbubble generation for enhanced pollutant removal in water treatment - Tschung-Il Kim; Mooyoung Han; Hyunju Park (Journal of Water Process Engineering, 2026)

Application of infrapatellar fat pad-derived stem cells after surgical reconstruction of a ruptured cranial cruciate ligament in a dog - Min-Gyeong Seo; Seil Park; Seonyoung Han; Chang-Hwan Moon; Kyu-Shik Jeong; Il-Hwa Hong (Veterinary Research Communications, 2026)

Comparative responses of fruit quality attributes, mineral nutrients, and targeted metabolites in fruit of early- to mid-season apple cultivars at harvest - Jinhee Lee; Hnin Phyu Lwin; Seung Yeon Han; Si-Eun Byeon; Hyowon Park; Theint Thandar Latt; Jiwon Park; Sooyeon Lim; Jong Taek Park; Ha-il Jung; Dagyeong Kwon; Jeong Hee Kim; et al. (Horticulture, Environment, and Biotechnology, 2026)

Comparison of surface-guided radiotherapy-based deep inspiration breath hold and continuous positive airway pressure techniques in left-sided breast cancer: dosimetric and workflow analysis - Su Chul Han; Jason Joon Bock Lee; Jin Dong Cho; Il Sun Jeong; Heerim Nam; Hyebin Lee (Physical and Engineering Sciences in Medicine, 2026)

White ginseng ethanol extract inhibits melanogenesis in B16F10 cells by regulating the microphthalmia-associated transcription factor/tyrosinase pathway - Min Jung Kim; Ye Jin Yang; Ji Woong Heo; Han Nim Choi; Chae Un Lim; Se Hyo Jeong; Hun Hwan Kim; Gon Sup Kim; Young Hun Kim; Ju-Hye Yang; Kwang Il Park (Molecular & Cellular Toxicology, 2026)

Formulation development of basroparib as a first-in-class tankyrase inhibitor using a microprecipitated bulk powder approach - Uk-Il Kim; Ravi Maharjan; Hyo-Kyung Han; Kyungjin Kim; Seong Hoon Jeong (Journal of Pharmaceutical Investigation, 2026)

Sustainable synthesis of polycarbonate-based non-isocyanate polyurethane via double metal cyanide catalysis - Chinh Hoang Tran; Han Su Lee; Ngoc Thanh Truong; Phuong Ngoc Nguyen; Nghiem Anh Tuan Le; Duy Du Bui; Chi Le Hoang Tran; Khoa Anh Trinh; Giang Ngoc Doan; Van Du Cao; Il Kim (Journal of Environmental Chemical Engineering, 2026)

Sprayable, crosslinker-free, and in situ-forming Schiff-based hydrogels based on oxidized sodium alginate and carbohydrazide-modified gelatin for rapid hemostasis - Ji Hye Yoo; Dae Hyeok Yang; Jae Hwan Choi; Haram Nah; Wheemoon Cho; Seung Yeon Lee; Jae Seo Lee; Han-Jun Kim; Gun-Jae Jeong; Heung Jae Chun; Dong Nyoung Heo; Il Keun Kwon (Carbohydrate Polymers, 2026)

Effect of water temperature and irradiance on growing crustose stage of Grateloupia divaricata (Rhodophyta) - Pyo Il Han; Beom-Sik Kim; Jong Won Park; Hyung Geun Kim; Chung Il Lee (Journal of Applied Phycology, 2026)

A Study on an Extrapolation Method for the Propulsive Performance of the Pumpjet Propulsor of a Submarine - Woo-Seok Jin; Moon-Chan Kim; Jin-Wook Kim; Il-Ryong Park; Han-Shin Seol (Journal of Marine Science and Engineering, 2026)
Accurately predicting the full-scale performance of submarines is challenging due to their complex propulsor systems and limited sea-trial information. This study investigated a full-scale extrapolation method from model tests for a submarine pumpjet propulsor, as a reliable method has not been established. Three extrapolation methods from ITTC reports were reviewed and applied to the pumpjet propulsor of the SUBOFF submarine, then compared with full-scale CFD results. Among the reviewed methods (Methods 1 to 3), Method 3, which separates the duct and stator as appendages of the hull and includes the entire pumpjet in the POW test but uses only the rotor’s force, was the most reasonable, but showed significant differences from the calculated results, especially in the PD. This study proposed a modified Method 3, improving it by adopting the continuity theory to predict the oncoming velocity of a rotor and by applying a correction factor for the drag of the duct and stator. The modified PJP extrapolation method 3 showed excellent agreement with the full-scale CFD analysis results across all propulsion coefficients, with a minimal error of 0.45% for PD. Despite the structural differences in PJPs, such as stators and longer ducts, velocity changes are dominated by the duct’s internal area. Therefore, the proposed extrapolation method is equally applicable to general ducted propellers.

A route planning method for small ships based on historical AIS data - Seong-Won Choi; Myung-Il Roh; In-Chang Yeo; Won-Chul Yoo; Seon-Do Han (Ocean Engineering, 2026)

γ-ray induced microstructure modulation for enhanced output performance of polyimide-based piezoelectric composites - Dong Yeol Hyeon; Gyoung-Ja Lee; Hyeon Jun Park; Dong Won Jeon; Han Uk Lee; Sung Beom Cho; Jaehun An; Nagamalleswara Rao Alluri; Young Hoon Jung; Changyeon Baek; HakSu Jang; SungHoon Kim; et al. (Chemical Engineering Journal, 2026)

Synergistic integration of high-pressure processing, pulsed electric fields, cold plasma, and UV light with bioactive compounds for enhanced food safety, quality, and shelf-life: new advances and mechanisms - Anand Kumar; Gebremichael Gebremedhin Hailu; Meijin Xv; Hui Qiu; Sun-Il Choic; Ok-Hwan Lee; Zefu Wang; Zongyuan Han; Shucheng Liu; Shuai Wei (Food and Humanity, 2025)

First Assessment of Coccolithophore-Driven Carbonate Flux in the Ulleung Basin, East Sea (Sea of Japan) - Sung Min An; Dong Han Choi; Young-Il Kim; Young Suk Chang; Jae Hoon Noh (Ocean Science Journal, 2025)

Epigenetic profiles integrated with transcriptomic reveal the difference between COPD and PRISm in KOCOSS-NIH - Eun-A Choi; Hyun Jeong Kim; Youlim Kim; Han Byul Jang; Yong Il Hwang; Young-Youl Kim; Kwang Ha Yoo; Hye-Ja Lee (Functional & Integrative Genomics, 2025)

Secondary metabolites from marine-derived fungus Aspergillus sp. SF6390 and their biological effects - Chi-Su Yoon; Fangfei Tang; Joung Han Yim; Il-Chan Kim; Jae Hak Sohn; Dong-Sung Lee; Haeun Kwon; Dongho Lee; Hyuncheol Oh (Natural Product Research, 2025)

Ship-hull mediated introduction risk of Colaconema formosanum: barnacle-associated dispersal and ecophysiological potential for coastal establishment - Ju-Hyoung Kim; Ye Rim Kim; Min Gui Jung; Eun Ju Kang; Kyoungsoon Shin; Bonggil Hyun; Jung-Hoon Kang; Seung Ho Baek; Il-Nam Kim; Jong Won Han; Jee Eun Lee; Hyung Woo Lee (Biological Invasions, 2025)

Joint inversion of apparent resistivity and frequency domain induced polarization data due to anomalous body ahead of the tunnel face - Un-Gyong Pak; Il-Gyong Ri; Gwang-Chol Jon; Sung-Jin Han; Song-Hyok Ri (Acta Geophysica, 2025)

Numerical Verification of an Anchor-Free Jack-Up Installation Method for Offshore Wind Turbine Structures Using Tugboat Fleet - Min Han; Young IL Park; A Ra Ko; Jin Young Sung; Jeong-Hwan Kim (Journal of Marine Science and Engineering, 2025)
With the rapid expansion of offshore wind power, efficient installation methods for 10 MW offshore wind turbines (OWTs) are increasingly being required. Conventional approaches using installation vessels, heavy-lift barges, and mooring systems incur high costs, long schedules, and weather-related constraints, particularly in harsh seas such as the West Sea and Jeju. This study investigates an anchor-free installation method for jack-up-type OWTs employing tugboats instead of specialized vessels. Environmental loads were estimated with MOSES and AQWA, and frequency-domain analyses were performed to evaluate wave responses and towline tensions. Results showed that maximum tensions remained below both the Safe Working Load of towlines and the Effective Bollard Pull of tugboats during all spudcan lowering stages. Even under conservative OPLIM conditions, feasibility was confirmed. The findings indicate that the proposed tug-assisted method ensures adequate station-keeping capability while reducing cost, construction time, and weather dependency, presenting a practical alternative for large-scale OWT installation.

The impact of the 2018 North Korea–United States summit on South Koreans’ altruism toward and trust in North Korean refugees - Han Il Chang; Woo Chang Kang (The Social Science Journal, 2025)

Phenotypic prevalence index: Diversity of polyphosphate-accumulating organisms (PAOs) and insights in unknown PAOs revealed by combined fluorescence-activated cell sorting (FACS) and 16S rRNA gene sequencing - Peisheng He; Yuan Yan; Jangho Lee; IL Han; Guangyu Li; Fabrizio Sabba; Zhen Jia; George F. Wells; April Z. Gu (Water Research, 2025)

DNA barcode and sequence related amplified polymorphism markers reveal phylogenetic relationship among Pinus species representing closed lineage divergence - Mi-Ryong Choe; Sam-Rang Song; Un–Hyang Ho; Jong–Gum Ri; Chung-Il Yo; Tong-Ryul Kim; Ok-Hyang Han; Il-Jin Kim; Chol-Ho Kang (Genetic Resources and Crop Evolution, 2025)

Unsupervised classification of iron ores based on elemental and isotopic signatures from atomic and molecular emissions of laser-induced plasma - Sung-Uk Choi; Sol-Chan Han; Jong-Il Yun (Analytica Chimica Acta, 2025)

Legacy and emerging persistent organic pollutants in sea turtles from Korean waters: Levels, profiles, and interspecies differences - Yelim Moon; Won Joon Shim; Sung Yong Ha; Gi Myung Han; Mi Jang; Il-Hun Kim; Hae-Rim Lee; Sang Hee Hong (Environmental Research, 2025)

Systemic toxicity and toxicokinetics study of self-assembled-micelle inhibitory RNA-targeting amphiregulin in cynomolgus monkeys following intravenous injection - Hyeon-Young Kim; Tae-Rim Kim; Sung-Hwan Kim; In-Hyeon Kim; Woong-Il Kim; Jun-Hong Park; Youngho Ko; Sungil Yun; Han-Oh Park; Jong-Choon Kim (Toxicological Research, 2025)

Role of heat shock proteins and analysis of gene expression in response to high temperatures in date palm (Phoenix dactylifera) - Seo-Won Yoo; Jae-Han Choi; Seok Won Jeong; Youn-Il Park; Young-Ji Byon; Man-Ho Oh (Genes & Genomics, 2025)

A representation method of pipe connections and routing space in pipe auto-routing using graph and octree structures - Min-Chul Kong; Myung-Il Roh; In-Su Han; Inseok Lee; Hyunseung Lee; Mijin Kim; Jeoungyoun Kim; Jinhyeong You (Ocean Engineering, 2025)

The role of tight junctions in the pathogenesis of inflammatory bowel disease: immune modulation and barrier dysfunction - Ji Woong Heo; Min Jung Kim; Ye Jin Yang; Han Nim Choi; Kwang Youn Kim; Tae Woo Oh; Ju-Hye Yang; Young Hun Kim; Kwang Il Park (Molecular & Cellular Toxicology, 2025)

Angelica gigas Nakai hot water extracts alleviate IL-6-induced ulcerative colitis by restoring intestinal barrier function - Ye Jin Yang; Min Jung Kim; Ji Woong Heo; Han Nim Choi; Dongbin Lee; Young Hun Kim; Kwang Il Park (Molecular & Cellular Toxicology, 2025)

Toxicity of diclofenac sodium salt after two weeks of daily intramuscular administration in cynomolgus monkeys - Sieun Yoo; Jung-Ho Noh; Hong-Soo Lee; Sang-Hee Lee; Eunji Choi; Dong-Il Kim; Seung Eui Min; Kang-Hyun Han; Sang Kyum Kim (Toxicological Research, 2025)

Correction: Angelica gigas Nakai hot water extracts alleviate IL-6-induced ulcerative colitis by restoring intestinal barrier function - Ye Jin Yang; Min Jung Kim; Ji Woong Heo; Han Nim Choi; Dongbin Lee; Young Hun Kim; Kwang Il Park (Molecular & Cellular Toxicology, 2025)

Effect of extracellular vesicles derived from oviductal and uterine fluid on the development of porcine preimplantation embryos - Ayeong Han; Ahmad Yar Qamar; Seonggyu Bang; Heyyoung Kim; Heejae Kang; Jun-Hyeong Kim; Kimyung Choi; Sung Ho Yun; Seung Il Kim; Islam M. Saadeldin; Sanghoon Lee; Jongki Cho (Theriogenology, 2025)

Paleoceanographic responses to sea level variability in the East Sea since the last glacial period: Multi-proxy approach - Kwangchul Jang; Germain Bayon; Yeongcheol Han; Youngkyu Ahn; Young Jin Joe; Yeong Ju Son; Seungmi Lee; Jae Hwa Jin; Eunji Byun; Seung-Il Nam (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Two new compounds from Apiospora xenocordella culture medium and their inhibitory effects on TNF-α-induced ROS generation and MMP-1 secretion - Haeun Kwon; Hee Woon Ann; Jin Su Lee; Jaeyoung Kwon; Keunwan Park; Yuanqiang Guo; Bang Yeon Hwang; Jae-Jin Kim; Joung Han Yim; Il-Chan Kim; Dae Sik Jang; Sullim Lee; et al. (Phytochemistry Letters, 2025)

Reactive metal–support interaction of In2O3/crystalline carbon hybrid support for highly durable and efficient oxygen reduction reaction electrocatalyst - Seung Min Woo; Han Seul Kim; Pil Ju Youn; Kyung Rog Lee; Gyu Mi Kang; Sang-Hoon You; Kug-Seung Lee; Yong-Tae Kim; Seung-Ho Yu; Jeong Hwan Han; Sung Jong Yoo; Il-Kyu Park (Chemical Engineering Journal, 2025)

Facile manufacturing solutions for ultra-durable flexible MXene micro-supercapacitors in 8-inch scale - Eunji Kim; Yunhui Choi; Hyeong Jin Kim; Hyeong Min Jin; Yeon-Wha Oh; Sanghee Jung; Il-Suk Kang; Hee Han; Jaewoo Roh; Il-Kwon Oh; Jinwoo Lee; Chi Won Ahn; et al. (Chemical Engineering Journal, 2025)

5-Fluorouracil induces hair loss by inhibiting β-catenin signaling and angiogenesis - Jung-Il Kang; Youn Kyung Choi; Sang-Chul Han; Jin Won Hyun; Young-Sang Koh; Jaeseong Oh; Hye-Jin Boo; Eun-Sook Yoo; Hee-Kyoung Kang (Chemico-Biological Interactions, 2025)

Immobilization of erythrosine dye in polysiloxane to fabricate a cost-effective renewable antibiotic film through visible light-induced singlet oxygen generation - Nakyeong Lee; Byeonghwak Bae; Won-Sik Han; Il-Kwon Bae; Jun-Yong Shin; Kang-Kyun Wang; Jae-Min Oh; Jin Kuen Park (Journal of Cleaner Production, 2024)

Glycyrrhiza uralensis extract improves dexamethasone-induced sarcopenia via regulating myostatin- and FoxO3a-mediated E3 ubiquitin ligase - Yulong Zheng; SoEun An; Ga-Yeon Kim; Ki-Soo Han; Young-Jin Baek; Il-Jun Kang (Food Bioscience, 2024)

Molecular evidence of internal carbon-driven partial denitrification in a mainstream pilot A-B system coupled with side-stream EBPR treating municipal wastewater - Da Kang; Yuan Yan; IL Han; Jangho Lee; Kester McCullough; Guangyu Li; Zijian Leo Wang; Peisheng He; Dongqi Wang; Stephanie Klaus; Ping Zheng; Varun Srinivasan; et al. (Water Research, 2024)

High-Speed Clearing and High-Resolution Staining for Analysis of Various Markers for Neurons and Vessels - Jung Min Park; Seock Hwan Choi; Eun-Shil Lee; Sang-Il Gum; Sungkuk Hong; Dong Sun Kim; Man-Hoon Han; Soung-Hoon Lee; Ji Won Oh (Tissue Engineering and Regenerative Medicine, 2024)

Enhancing viral detection in aquaculture water through virus-microplankton associations and plankton net concentration - Yoonhang Lee; Hyo-Young Kang; HyeongJin Roh; Dongbin Yun; Jiyeon Park; Ju-Yeop Lee; Young-Ung Heo; Sung Youl Hong; Gwang-Il Jang; Mun-Gyeong Kwon; So-Ri Han; Sung-Hyun Kim; et al. (Aquaculture, 2024)

Green and efficient method to acquire high-value phycobiliprotein from microalgal biomass involving deep eutectic solvent-based ultrasound-assisted extraction - Ke Li; Chunxue Jiang; Sang-Il Han; Seulgi Kang; Jingyan Chen; Danbi Won; Yua Kang; Boyeon Bae; Yoon-E Choi; Hyung Sik Kim; Jeongmi Lee (Food Chemistry, 2024)

Mobile phone users as pseudo-brokers in clientelism: evidence from Africa - Han Il Chang; Su-Hyun Lee (The Social Science Journal, 2024)

Luxury application of biochar does not enhance rice yield and methane mitigation: a review and data analysis - Husna Israt Pia; Nuri Baek; Seo-Woo Park; Eun-Seo Shin; Sun-Il Lee; Han-Yong Kim; Shuirong Tang; Weiguo Cheng; Jin-Hyeob Kwak; Hyun-Jin Park; Woo-Jung Choi (Journal of Soils and Sediments, 2024)
Purpose It is unclear whether a higher biochar (BC) application rate enhances rice ( Oryza sativa L.) yield and reduces CH 4 emissions. This study investigated changes in rice yield and CH 4 emissions with varying BC application rates. Methods Data on rice yield and CH 4 emission from paddies amended with or without BC were collected from the literature, and the biochar effects were analyzed using the data set. Results Across the biochar application rate from 2 to 48 t ha -1 , the rice yield increased (by 10.8%) while the area-scaled (by 14.4%) and yield-scaled CH 4 emission (by 22.2%) decreased. However, the correlation of BC application rates with rice yield and CH 4 mitigation was not significant, implying that a higher BC application rate did not enhance rice yield and CH 4 reduction. Interestingly, for a data set showing increased rice yield and decreased CH 4 emission by BC, the magnitude of change in the rice yield and CH 4 mitigation per unit weight of BC (1 t ha -1 ) decreased with an increase in the BC application rate. These results suggest that BC effects on rice yield and CH 4 mitigation are not additive, probably because of the decreases in the inherent capacity of unit weight of BC to enhance rice yield and reduce CH 4 emission, which might be caused by the adverse effects of toxic compounds contained in BC, losses of BC, and a higher degree of nutrient immobilization by BC. Conclusions Annual BC application at a low rate (e.g., 2 t ha -1 ) rather than a luxury application may be an effective and economical strategy for long-term rice yield enhancement and CH 4 mitigation using BC.

The effect of exopolysaccharides from EMS-induced Porphyridium cruentum mutant on human epidermal and dermal layers - Sang-Il Han; Young Mok Heo; Min Seo Jeon; Seoyeon Kyung; Seunghyun Kang; Soon-Jae Kwon; Jai Hyunk Ryu; Jae Hoon Kim; Joon-Woo Ahn (Frontiers in Marine Science, 2024)
Introduction Microalgae biotechnology utilizes species like Porphyridium cruentum for their valuable phycobiliproteins and exopolysaccharides, which have potential industrial applications and health benefits, particularly in skin condition improvement. Methods A mutant of P. cruentum LIMS-PS-1061 was developed through ethyl methanesulfonate mutagenesis and subsequent colony screening to study changes in its biomass production and pigment composition under different lighting conditions. Results and discussion The mutant exhibited a 33.9% increase in dry weight under white light compared to the wild type. Despite maintaining the total pigment content, specific components changed significantly: chlorophyll content decreased 2.20- and 3.61-fold under white and blue light respectively, while phycobiliproteins increased 1.59- and 1.23-fold under the same conditions. These alterations suggest a compensatory mechanism for maintaining photosynthetic capacity. Furthermore, the exopolysaccharides of P. cruentum upregulated genes related to skin moisturization, barrier enhancement, and elasticity, and promoted wound healing through fibroblast migration. This supports the proposed mechanism of action for P. cruentum’s exopolysaccharides in improving human skin conditions by integrating the effects of aquaporin 3, filaggrin, involucrin, loricrin, elastin, and fibrillin-1.

Comparative pangenome analysis of Aspergillus flavus and Aspergillus oryzae reveals their phylogenetic, genomic, and metabolic homogeneity - Dong Min Han; Ju Hye Baek; Dae Gyu Choi; Min-Seung Jeon; Seong-il Eyun; Che Ok Jeon (Food Microbiology, 2024)

Synergistic structural and electronic influences of Pt bead catalysts on dehydrogenation activity for liquid organic hydrogen carriers - Seungmok Han; Chang-il Ahn; Byeong Jo Shim; Euirim On; Chan Kim; Hyuntae Sohn; Hyangsoo Jeong; Yongmin Kim; Chang Won Yoon (Chemical Engineering Journal, 2024)

Comammox and unknown ammonia oxidizers contribute to nitrite accumulation in an integrated A-B stage process that incorporates side-stream EBPR (S2EBPR) - Yuan Yan; Jangho Lee; IL Han; Zijian Wang; Guangyu Li; Kester McCullough; Stephanie Klaus; Da Kang; Dongqi Wang; Anand Patel; Jim McQuarrie; Beverley M. Stinson; et al. (Water Research, 2024)

Identifying the external N and Hg inputs to the estuary ecosystem based on the triple isotopic information (δ15NNO3, Δ17ONO3 and δ18ONO3) - Haryun Kim; Hye Seon Kim; Jihee Kim; Dongwoo Yang; Kitack Lee; Kitae Kim; Giyoung Ock; Hyung-Geun Park; Rebecca S. Robinson; Min-Seob Kim; Geun-Ha Park; Ju-Hyoung Kim; et al. (Marine Pollution Bulletin, 2024)

Revisiting the role of Acinetobacter spp. in side-stream enhanced biological phosphorus removal (S2EBPR) systems - Yuan Yan; IL Han; Jangho Lee; Guangyu Li; Varun Srinivasan; Kester McCullough; Stephanie Klaus; Da Kang; Dongqi Wang; Peisheng He; Anand Patel; Charles Bott; et al. (Water Research, 2024)

Side-Stream Enhanced Biological Phosphorus Removal (S2EBPR) enables effective phosphorus removal in a pilot-scale A-B stage shortcut nitrogen removal system for mainstream municipal wastewater treatment - Dongqi Wang; Il Han; Kester McCullough; Stephanie Klaus; Jangho Lee; Varun Srinivasan; Guangyu Li; Zijian Leo Wang; Charles B. Bott; Jim McQuarrie; Beverley M. Stinson; Christine deBarbadillo; et al. (Water Research, 2024)

Angular dihydropyranocoumarins from the flowers of Peucedanum japonicum and their aldo-keto reductase inhibitory activities - Jisu Park; Trung Huy Ngo; Sunil Babu Paudel; Yun-Seo Kil; Ga-Hee Ryoo; Chang Hyun Jin; Hong-Il Choi; Chan-Hun Jung; MinKyun Na; Joo-Won Nam; Ah-Reum Han (Phytochemistry, 2024)

Constructing green superhydrophilic and superoleophobic COFs-MOFs hybrid-based membrane for efficiently emulsion separation and synchronous removal of microplastics, dyes, and pesticides - Shan Peng; Haobo Ma; Xiaoyan Hao; Ruimeng Han; Xiaoyu Ji; Lei Wang; Yanyan Fang; Kyongjin Pang; Kwon Il-Ho; Xiaoxin Chen (Environmental Research, 2024)

One-step wet-spinning of conducting polymer and cellulose nanofiber composites for fiber-type organic electrochemical transistors - Minhu Huang; Seunghyeon Lee; Il-Young Jo; Hyunbeen Park; Bong Sup Shim; Myung-Han Yoon (Carbohydrate Polymers, 2024)

Modeling ozone deposition on bulk grains and ozone deposition in columns of wheat grains - Su Gil Kim; Un Yong Paek; Ae Chun Ri; Song Ho Kim; Il Song Han; Songchol Hong (Journal of Stored Products Research, 2023)

Age and Growth of Shotted Halibut, Eopsetta grigorjewi (Herzenstein, 1890), in the West Sea of Korea - Dong-Hyuk Choi; Byoung-Il Youn; Kyeong-Ho Han; Dae-Hyeon Kwon; Soo-Jeong Lee (Journal of Marine Science and Engineering, 2023)
To investigate the age and growth characteristics of shotted halibut, Eopsetta grigorjewi, in the West Sea of Korea, the samples were collected using gill nets throughout 2019. A total of 861 specimens (693 females and 168 males) were analyzed. The BW-TL relations were BW = 0.0034TL3.3278 (R2 = 0.8716) for females and BW = 0.0031TL3.3359 (R2 = 0.8860) for males. This analysis revealed that males exhibited a larger growth rate than females (p

Spatiotemporal informer: A new approach based on spatiotemporal embedding and attention for air quality forecasting - Yang Feng; Ju-Song Kim; Jin-Won Yu; Kuk-Chol Ri; Song-Jun Yun; Il-Nam Han; Zhanfeng Qi; Xiaoli Wang (Environmental Pollution, 2023)

Endophyte Bacillus tequilensis improves the growth of microalgae Haematococcus lacustris by regulating host cell metabolism - Min Seo Jeon; Sang-Il Han; Joon-Woo Ahn; Jong-Hyun Jung; Jong-Soon Choi; Yoon-E Choi (Bioresource Technology, 2023)

Effects of extracellular vesicles derived from steroids-primed oviductal epithelial cells on porcine in vitro embryonic development - Seonggyu Bang; Ahmad Yar Qamar; Xun Fang; Heyyoung Kim; Ayeong Han; Heejae Kang; Dabin Cha; Joohyun Shim; Jun-Hyeong Kim; Kimyung Choi; Sung Ho Yun; Hayoung Lee; et al. (Theriogenology, 2023)

Length–weight relationships and condition factors of six notothenioid fish species occurring off King George Island and Northern Victoria Land (Antarctica) - Jihun Kim; Seungyeon Lee; Phuong Thi Nguyen; Dong-Won Han; IL-Chan Kim; Jin-Hyoung Kim (Polar Biology, 2023)
This research was conducted to study length–weight relationships (LWR) and condition factors of six Antarctic notothenioidei fish species including blackfin icefish ( Chaenocephalus aceratus ), single-angle icefish ( Chionodraco hamatus ), marbled rockcod ( Notothenia rossii ), black rockcod ( Notothenia coriiceps ), emerald rockcod ( Trematomus bernacchii ), and dusky rockcod ( Trematomus newnesi ) from the King Sejong Station on King George Island and Jang Bogo Station on the Northern Victoria Land. A total of 232 specimens were collected by fishing on the icebreaking research vessel ARAON from December 2020 to February 2021. The LWR parameters and condition factors differed depending on species, which can be affected by their distribution, species characteristics, and gravidity status. The exponent b values in LWR ( W = aL b ) ranged from 2.593 to 5.184. Four species including C. aceratus , C. hamatus , N. rossii , and T. bernacchii followed positive allometric growth, T. newnesi followed negative allometric growth, and only N. coriiceps showed isometric growth. These results can be helpful in understanding the ecological and growth conditions of six fish species living in the Antarctic Ocean, providing more information for future research on Antarctic fish.

First record of Macaca mulatta (Cercopithecidae: Papionini) from the Taedong River Basin, the Democratic People’s Republic of Korea - Kum Sik Han; Kwang Sik So; Rye Sun Choe; Jun Chol Kang; Il Kang; Chol Ung Ri (Palaeoworld, 2023)

Effects of triazine herbicide terbutryn on physiological responses and gene expression in Alexandrium catenella - Qikun Xing; Young Woo Kim; Ji-Sook Park; Young-Seok Han; Charles Yarish; Hyun Il Yoo; Jang K. Kim (Journal of Applied Phycology, 2023)

Differential responses of bulb quality attributes, mineral nutrient contents, and targeted major metabolites in onion bulbs after long-term commercial cold storage - Hnin Phyu Lwin; Seung Yeon Han; Si-Eun Byeon; Jinhee Lee; Jingi Yoo; Ha-il Jung; Jinwook Lee (Horticulture, Environment, and Biotechnology, 2023)

Functional divergence of two closely related carboxylesterases in pepper (Capsicum annuum L.) - Yun-Jeong Han; Ha-Young Kang; Young Soon Kim; Jeong-Il Kim (Plant Biotechnology Reports, 2023)

High-capacity/high-rate hybrid column for high-performance ion exchange - Sung Il Yoon; Minhee Han; Haribandhu Chaudhuri; Yeoung-Sang Yun (Environmental Research, 2023)

Crosshole radio electromagnetic tomography using apparent source intensity and logarithmic barrier - Il-Gyong Ri; Un-Gyong Pak; Sung-Jin Han; Chol-Jin Yun (Journal of Applied Geophysics, 2023)

Adipose stem cell transplantation using adhesive protein-based viscous immiscible liquid for cartilage reconstruction - Seong-Woo Maeng; Ji-Yun Ko; Tae Yoon Park; Jinyoung Yun; So Hyun Park; Sang Jun Han; Kye Il Joo; Seongmin Ha; Mingoo Jee; Gun-Il Im; Hyung Joon Cha (Chemical Engineering Journal, 2023)

Age and Growth Characteristics of Okamejei kenojei in the West Sea of South Korea According to Coronal Vertebral Microstructure - Byoung-Il Youn; Dong-Hyuk Choi; Tae-Hyoung Roh; Seung-Hwan Lee; Kyeong-Ho Han; Dae-Hyeon Kwon; Maeng-Jin Kim (Fishes, 2023)
In this study, the growth and age characteristics of Okamejei kenojei in the West Sea of South Korea were examined, and specimens were collected by bottom trawls from January to December 2019. The relationship between disc width (L) and body weight (W) was W = 6.1 × 10−3 L3.40. Age was determined by measuring annuli on the vertebral centrum surface, which forms around June every year. The spawning period was extrapolated from monthly changes of the gonadosomatic index in June–July. The relationship between the vertebral centrum radius and disc width, which was analyzed separately for females and males, was determined as L = 16.159R0.6145 and L = 15.543R0.6851, respectively. Finally, O. kenojei growth, that is, the disc width (L) at a certain age (t), was expressed using the von Bertalanffy growth equation as Lt = 58.70(1 − e−0.21(t+0.12)) for females and Lt = 53.94(1 − e−0.26(t+0.05)) for males. This study provides basic data on the age characteristics of O. kenojei for future research and more efficient fish stock management.

Regime shift increase in East Asia's summer extreme hot day frequency across the late 1990s - Yong‐Han Lee; Sang‐Wook Yeh; Jin‐Sil Hong; Jongsoo Shin; Soon‐Il An (International Journal of Climatology, 2023)
Here we analysed the long‐term change in extreme hot days (EHDs) in East Asia during boreal summer (June–July–August) since 1979, where EHDs was defined as days exceeding or equalling the 90th percentile threshold of the climatological (1991–2020) daily and . EHDs frequency occurrence in East Asia during summer showed not only an increasing trend but also a distinct regime shift increase since the late 1990s. Based on this regime shift, we divided these years into two periods, P1 (1979–1998) and P2 (1999–2021), and found that different physical processes operated for each period's EHDs variability. P2's EHDs was related to the stationary wave originating from both the North Atlantic Ocean and the Indo‐Pacific warm pool, but these influences did not appear in P1. To investigate whether the observed regime shift increase was caused by natural variability or greenhouse gas concentration increases, we conducted a CO 2 quadrupling experiment as well as a present‐day experiment with a fixed CO 2 concentration using the Community Earth System Model with 28 ensemble members. We demonstrated that the regime shift increase of East Asian EHDs occurrences was due to increasing greenhouse gas concentrations. We further discussed the influence of Arctic sea ice reduction due to global warming on EHDs occurrences in East Asia.

Data-driven modeling of multimode chemical process: Validation with a real-world distillation column - Yeongryeol Choi; Bhavana Bhadriaju; Hyungtae Cho; Jongkoo Lim; In-Su Han; Il Moon; Joseph Sang-Il Kwon; Junghwan Kim (Chemical Engineering Journal, 2023)

Tracing the depth-dependent changes in organic carbon and nutrient fluxes using high-resolution 228Ra profiles in the upper East Sea (Japan Sea) - Hyung-Mi Cho; Yongjin Han; Young-Il Kim; Cheolmin Baek; Guebuem Kim (Frontiers in Marine Science, 2022)
Vertical profiles of 228 Ra (half-life: 5.75 years) in the ocean provide valuable information on water mixing and ages of the upper ocean. However, its application is hampered by extremely low levels of 228 Ra in the deep ocean. In this study, we measured high-resolution 228 Ra/ 226 Ra ratio profiles (>21 depths) in the East Sea (Japan Sea) by mooring Mn-fiber. Using the measured 228 Ra profile from 228 Ra/ 226 Ra ratios and 226 Ra activities, together with other previously published data, we estimated the vertical eddy diffusivity (8.7–9.6 cm 2 s -1 ) in the permanent thermocline and water ages (10–15 years) in the upper 500–1000 m range. The estimated decomposition rate of organic carbon based on oxygen utilization rates using Ra-ages between 100 and 1000 m was 4.4 ± 0.8 mol C m -2 yr -1 . Our results show that ~50% of the upward nutrients through 100 m support export production, and that dissolved organic carbon accounts for ~20% of carbon export. This 228 Ra approach provides a holistic understanding of carbon and nutrient cycles in the ocean.

Improvement of methods for analysing sucrose acetate isobutyrate (SAIB) in soft drinks using GC-FID and evaluating antioxidant effects in the SAIB emulsion system - Se-jeong Lee; Min-seop Kwon; Xionggao Han; Xiao Men; Geon Oh; Sun-Il Choi; Ok-Hwan Lee (Food Additives & Contaminants: Part A, 2022)

Geochemistry and zircon U-Pb-Hf isotopes of igneous rocks associated with the Dongnam Fe-Mo skarn deposit, Taebaeksan Basin, South Korea - Il-Hwan Oh; Sang-Mo Koh; Chul-Ho Heo; Bum Han Lee; Jieun Seo; Sang-Gun No; Seong-Jun Cho; Bong Chul Yoo (Geosciences Journal, 2022)

Spawning Period and Size at Maturity of the Ocellate Spot Skate Okamejei kenojei in the West Sea of Korea - Byoung-Il Youn; Dong-Hyuk Choi; Seung-Hwan Lee; Kyeong-Ho Han; Seung-Jong Lee; Dae-Hyeon Kwon; Maeng-Jin Kim (Journal of Marine Science and Engineering, 2022)
This study aimed to investigate the gonadal development process and size at maturity of the ocellate spot skate Okamejei kenojei (Müller and Henle, 1841). In total, 1234 specimens were collected from the center of the Korean West Sea between January 2019 and December 2020. The maturity stage of the gonads of each individual was determined visually based on size, color, and egg size. To estimate the spawning period, each specimen was measured for disc width, body weight, and gonad weight, and the monthly gonadosomatic index (GSI) was derived. The GSI of the specimens peaked in April and May, and the main spawning period occurred during June and July. Egg capsules were first observed in specimens collected in March and were most commonly observed in specimens collected in July (56.8%). The maturity ogives for disc widths of female specimens at 50%, 75%, and 97.5% maturity were 26.6, 27.9, and 30.8 cm, respectively, whereas those of male specimens were 26.2, 27.5, and 30.7 cm. The findings of this study provide basic information on reproductive ecology related to the fertility of the ocellate spot skate.

Infectivity and Transmissibility of Acute Hepatopancreatic Necrosis Disease Associated Vibrio parahaemolyticus in Frozen Shrimp Archived at −80 °C - Chorong Lee; Hye Jin Jeon; Bum Keun Kim; Seong-Kyoon Choi; Sumi Kim; Gwang Il Jang; Ji Hyung Kim; Jee Eun Han (Fishes, 2022)
Acute hepatopancreatic necrosis disease (AHPND) caused by Vibrio parahaemolyticus (VpAHPND) has been reported in commodity shrimp, but the potential risk of its global spread via frozen shrimp in the shrimp trade is yet to be fully explored. We hypothesized that frozen shrimp with AHPND could be a source of VpAHPND transmission; thus, the infectivity of frozen shrimp with AHPND was evaluated using a shrimp bioassay. To prepare infected frozen shrimp, 12 Penaeus vannamei (average weight, 2 g) were exposed to VpAHPND by immersion in water with a VpAHPND concentration of 1.55 × 107 CFU mL−1; once dead, the shrimp were stored at −80 °C for further analysis. After two weeks, a PCR assay was used to confirm AHPND positivity in frozen shrimp (n = 2), and VpAHPND was reisolated from the hepatopancreases of these shrimp. For the infectivity test, 10 P. vannamei (average weight, 4 g) were fed with the hepatopancreases of VpAHPND -infected frozen shrimp (n = 10). After feeding, 70% of the shrimp died within 118 h, and the presence of VpAHPND was confirmed using a PCR assay and histopathology examination; moreover, VpAHPND was successfully reisolated from the hepatopancreases of the dead shrimp. We are the first to evaluate the potential transmissibility of VpAHPND in frozen shrimp, and our results suggest that frozen shrimp with AHPND are a potential source of disease spreading between countries during international trade.

Organic Carbon Oxidation in the Sediment of the Ulleung Basin in the East Sea - Jae Seong Lee; Sung-Han Kim; Ju-Wook Baek; Kyung-Tae Kim; Dongseon Kim; Young-il Kim; Won-Chan Lee; Sung-Uk An; Chang Hwan Kim; Chan Hong Park; Sokjin Hong (Journal of Marine Science and Engineering, 2022)
We characterized the biogeochemical organic carbon (Corg) cycles in the surface sediment layer of the Ulleung Basin (UB) of the East Sea. The total oxygen uptake (TOU) rate and the diffusive oxygen uptake (DOU) rate of the sediment were measured using an autonomous in situ benthic lander equipped with a benthic chamber (KIOST BelcII) and a microprofiler (KIOST BelpII). The TOU rate was in the range of 1.51 to 1.93 mmol O2 m−2 d−1, about double the DOU rate. The high TOU/DOU ratio implies that the benthic biological activity in the upper sediment layer is one of the important factors controlling benthic remineralization. The in situ oxygen exposure time was about 20 days, which is comparable to the values of other continental margin sediments. The sedimentary Corg oxidation rates ranged from 6.4 to 6.5 g C m−2 yr−1, which accounted for ~2% of the primary production in UB. The Corg burial fluxes ranged from 3.14 ± 0.12 to 3.48 ± 0.60 g C m−2 yr−1, corresponding to more than 30% of the deposited Corg buried into the inactive sediment deep layer.

Baroclinic Effect on Inner-Port Circulation in a Macro-Tidal Estuary: A Case Study of Incheon North Port, Korea - Jae-Soon Jeong; Seung-Buhm Woo; Han Soo Lee; Bon-Ho Gu; Jong Wook Kim; Jin Il Song (Journal of Marine Science and Engineering, 2022)
This study investigated the flow patterns and affecting factors in the North Port of Incheon, South Korea, to understand the inner-port circulation characteristics by applying an unstructured grid finite volume community ocean model (FVCOM) together with a field survey. The FVCOM considered the tide, river discharge, surface winds, and atmospheric pressure with the highest resolution of 50 m around the port. The model results were validated with current velocity and salinity observations. In the main channel, the difference in salinity between the sea surface and bottom increased during the neap tide due to weakened tidal currents, thus strengthening the stratification. However, at the inner port, strong stratification was observed during spring tide as the near-surface freshwater from upstream of the estuary moved relatively farther south of the port than that during the neap tide. Freshwater flowed into the port during the flood current and was trapped in the semi-closed geometry of the inner port. The horizontal salinity gradient between the trapped fresher water in the port and saltier water in the main channel increased during the flood current. As a result, density-driven circulations associated with near-bed currents towards the port were maintained for more than 3 h after high tide. This result implies that the baroclinic effect, mainly due to the salinity gradient in the North Port, could significantly affect residual circulation at the inner harbor in a macro-tidal environment and the mass transport mechanism, such as sediment transport. In general, such enhanced baroclinic effects due to salinity and tides are not limited to the North Port and can have greater effects on inner-port circulation in other macro-tidal harbors that suffer from severe sedimentation problems.

Surface-Modifying Effect of Zwitterionic Polyurethane Oligomers Complexed with Metal Ions on Blood Compatibility - Dong-Heon Ga; Chung-Man Lim; Yoonsun Jang; Tae Il Son; Dong Keun Han; Yoon Ki Joung (Tissue Engineering and Regenerative Medicine, 2022)

JAK2 regulates paclitaxel resistance in triple negative breast cancers - Jongmin Han; Jihui Yun; Mingji Quan; Wonyoung Kang; Ji-Gwang Jung; Woohang Heo; Songbin Li; Kyu Jin Lee; Hye-Youn Son; Ju Hee Kim; Jaeyong Choi; Dong-Young Noh; et al. (Journal of Molecular Medicine, 2021)

CRISPR/Cas9-mediated mutation of 5-oxoprolinase gene confers resistance to sulfonamide compounds in Arabidopsis - Ga-Jin Baeg; Seong-Hyeon Kim; Da-Min Choi; Sharanya Tripathi; Yun-Jeong Han; Jeong-Il Kim (Plant Biotechnology Reports, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Comparative Genomics and Transcriptomics Depict Marine Algicolous Arthrinium Species as Endosymbionts That Help Regulate Oxidative Stress in Brown Algae - Young Mok Heo; Seung-Yoon Oh; Kyeongwon Kim; Sang-Il Han; Sun Lul Kwon; Yeonjae Yoo; Dongjun Kim; Jong Seong Khim; Seunghyun Kang; Hanbyul Lee; Jae-Jin Kim (Frontiers in Marine Science, 2021)
The whole genome and transcriptome analyses were performed for prediction of the ecological characteristics of Arthrinium and the genes involved in gentisyl alcohol biosynthesis. Whole genome sequences of A. koreanum KUC21332 and A. saccharicola KUC21221 were analyzed, and the genes involved in interspecies interaction, carbohydrate-active enzymes, and secondary metabolites were investigated. Three of the seven genes associated with interspecies interactions shared by four Arthrinium spp. were involved in pathogenesis. A. koreanum and A. saccharicola exhibit the enzyme profiles similar to those observed in plant pathogens and endophytes rather than saprobes. Furthermore, six of the seven metabolites of known clusters identified in the genomes of the four Arthrinium spp. are associated with plant virulence. These results indicate that Arthrinium spp. are potentially pathogenic to plants. Subsequently, different conditions for gentisyl alcohol production in A. koreanum were established, and mRNA extracted from cultures of each condition was subjected to RNA-Seq to analyze the differentially-expressed genes. The gentisyl alcohol biosynthetic pathway and related biosynthetic gene clusters were identified, and gentisyl alcohol biosynthesis was significantly downregulated in the mannitol-supplemented group where remarkably low antioxidant activity was observed. These results indicate that gentisyl alcohol production in algicolous Arthrinium spp. is influenced by mannitol. It was suggested that the algicolous Arthrinium spp. form a symbiotic relationship that provides antioxidants when the photosynthetic activity of brown algae decreases in exchange for receiving mannitol. This is the first study to analyze the lifestyle of marine algicolous Arthrinium spp. at the molecular level and suggests a symbiotic mechanism with brown algae. It also improves the understanding of fungal secondary metabolite production via identification of the gentisyl alcohol biosynthetic gene clusters in Arthrinium spp.

Rapid green synthesis of silver nanoparticles using sulfated polysaccharides originating from Porphyridium cruentum UTEX 161: evaluation of antibacterial and catalytic activities - Min Seo Jeon; Sang-Il Han; Yun Hwan Park; Ho Seon Kim; Yoon-E Choi (Journal of Applied Phycology, 2021)

Collinsella acetigenes sp. nov., an Anaerobic Actinobacterium Isolated from Human Feces, and Emended Description of the Genus Collinsella and Collinsella aerofaciens - Kook-Il Han; Ji-Sun Kim; Mi Kyung Eom; Keun Chul Lee; Min Kuk Suh; Han Sol Kim; Seung-Hwan Park; Ju Huck Lee; Se Won Kang; Jam-Eon Park; Byeong Seob Oh; Seoung Woo Ryu; et al. (Current Microbiology, 2021)

Tiller Outgrowth in Rice (Oryza sativa L.) is Controlled by OsGT1, Which Acts Downstream of FC1 in a PhyB-Independent Manner - Vikranth Kumar; Sung Hoon Kim; Moch Rosyadi Adnan; Jung Heo; Jin Hee Jeong; Ryza A. Priatama; Jeung Joo Lee; Chul Min Kim; Byoung Il Je; Soon Ju Park; Yuan Hu Xuan; Chang-deok Han (Journal of Plant Biology, 2021)

RNA-sequencing identification and validation of genes differentially expressed in high-risk adenoma, advanced colorectal cancer, and normal controls - Namjoo Kim; Jeong-An Gim; Beom Jae Lee; Byung il Choi; Seung Bin Park; Hee Sook Yoon; Sang Hee Kang; Seung Han Kim; Moon Kyung Joo; Jong-Jae Park; Chungyeul Kim; Han-Kyeom Kim (Functional & Integrative Genomics, 2021)

Improved numerical inverse Laplace transformation to improve the accuracy of type curve for analyzing well-testing data - Song Chol Kim; Yong Il Song; Chol Gwang Han (Acta Geophysica, 2021)

Simple estimation of green area rate using image analysis and quantitative traits related to plant architecture and biomass in rice seedling - Kwang-O. Jong; Kwang-Myong Han; Son-Il Kwak; Yu-Jin Jang; Chol-Ho; Kwang -Phil Kim (Theoretical and Experimental Plant Physiology, 2021)

Generation and Characterization of a Specific Polyclonal Antibody against Arabidopsis thaliana Phytochrome-Interacting Factor 3 - Da-Min Choi; Jae-Yong Cho; Woe-Yeon Kim; Yun-Jeong Han; Jeong-Il Kim (Journal of Plant Biology, 2021)

Application of alginate microparticles incorporating formalin-inactivated Streptococcus parauberis for oral vaccination in olive flounder - Kwang Il Kim; Eun Young Min; Tae-Ho Kim; Hye Sung Choi; Hyun-Ja Han (Aquaculture International, 2021)

Co-cultivation of Euglena gracilis and Pseudoalteromonas sp. MEBiC 03607 for paramylon production - Min Seo Jeon; Sang-Il Han; Jee Young Kim; Yoon-E Choi (Journal of Applied Phycology, 2020)

Prediction of Ocean Weather Based on Denoising AutoEncoder and Convolutional LSTM - Ki-Su Kim; June-Beom Lee; Myung-Il Roh; Ki-Min Han; Gap-Heon Lee (Journal of Marine Science and Engineering, 2020)
The path planning of a ship requires much information, and one of the essential factors is predicting the ocean environment. Ocean weather can generally be gathered from forecasting information provided by weather centers. However, these data are difficult to obtain when satellite communication is unstable during voyages, or there are cases where forecast data for a more extended period of time are needed for the operation of the fleet. Therefore, shipping companies and classification societies have attempted to establish a model for predicting the ocean weather on its own. Historically, ocean weather has been primarily predicted using empirical and numerical methods. Recently, a method for predicting ocean weather using deep learning has emerged. In this study, a deep learning model combining a denoising AutoEncoder and convolutional long short-term memory (LSTM) was proposed to predict the ocean weather worldwide. The denoising AutoEncoder is effective for removing noise that hinders the training of deep learning models. While the LSTM could be used as time-series inputs at specific points, the convolutional LSTM can use time-series images as inputs, making them suitable for predicting a wide range of ocean weather. Herein, using the proposed model, eight parameters of ocean weather were predicted. The proposed learning model predicted ocean weather after one week, showing an average error of 6.7%. The results show the applicability of the proposed learning model for predicting ocean weather.

NH4+ Suppresses NO3–-Dependent Lateral Root Growth and Alters Gene Expression and Gravity Response in OsAMT1 RNAi Mutants of Rice (Oryza sativa) - Vikranth Kumar; Sung Hoon Kim; Ryza A. Priatama; Jin Hee Jeong; Moch Rosyadi Adnan; Bernet Agung Saputra; Chul Min Kim; Byoung Il Je; Soon Ju Park; Ki Hong Jung; Kyung Min Kim; Yuan Hu Xuan; et al. (Journal of Plant Biology, 2020)

Differential manifestation of ocular phenotypes in TALEN-mediated p19arf knockout FVB/N and C57BL/6J mouse lines - Jin-Sung Park; Joo-Il Kim; Hyun-Jin Lim; Soo-Kyung Ryu; Euna Kwon; Kang-Min Han; Ki-Taek Nam; Han-Woong Lee; Byeong-Cheol Kang (Genes & Genomics, 2020)

Comamonas flocculans sp. nov., a Floc-Forming Bacterium Isolated from Livestock Wastewater - Dong-Hyun Kim; Kook-Il Han; Hae-Jun Kwon; Mi-Gyeong Kim; Young-Guk Kim; Doo-Ho Choi; Keun Chul Lee; Min Kuk Suh; Han Sol Kim; Jung-Sook Lee; Jong-Guk Kim (Current Microbiology, 2020)

Wax-printed well pads and colorimetric LAMP detection of ApxIA toxin gene - SeonHyung Lee; Ji Hun Kim; Beom-Ku Han; Won-Il Kim; Byung-Kwan Cho; Sung Min Woo; Yang-Hoon Kim; Ji-Young Ahn (Molecular & Cellular Toxicology, 2020)

Control of a toxic cyanobacterial bloom species, Microcystis aeruginosa, using the peptide HPA3NT3-A2 - Sang-Il Han; Sok Kim; Ki Young Choi; Changsu Lee; Yoonkyung Park; Yoon-E Choi (Environmental Science and Pollution Research, 2019)

Evaluating the impact of suramin additive on CHO cells producing Fc-fusion protein - Jin-Hyuk Lim; Hyun-Myoung Cha; Hye-Jin Han; Dong-Il Kim (Biotechnology Letters, 2019)

Application of CRISPR/Cas9-mediated gene editing for the development of herbicide-resistant plants - Yun-Jeong Han; Jeong-Il Kim (Plant Biotechnology Reports, 2019)

Vildagliptin, an Anti-diabetic Drug of the DPP-4 Inhibitor, Induces Vasodilation via Kv Channel and SERCA Pump Activation in Aortic Smooth Muscle - Mi Seon Seo; Hongliang Li; Jin Ryeol An; In Duk Jung; Won-Kyo Jung; Kwon-Soo Ha; Eun-Taek Han; Seok-Ho Hong; Il-Whan Choi; Won Sun Park (Cardiovascular Toxicology, 2019)

Brassinosteroids facilitate xylem differentiation and wood formation in tomato - Jinsu Lee; Seahee Han; Hwa-Yong Lee; Bomi Jeong; Tae-Young Heo; Tae Kyung Hyun; Kyunghwan Kim; Byoung Il Je; Horim Lee; Donghwan Shim; Soon Ju Park; Hojin Ryu (Planta, 2019)

Neuregulin1 Attenuates H2O2-Induced Reductions in EAAC1 Protein Levels and Reduces H2O2-Induced Oxidative Stress - Jun-Ho Lee; Ji-Young Yoo; Han-byeol Kim; Hong-Il Yoo; Dae-Yong Song; Sun Seek Min; Tai-Kyoung Baik; Ran-Sook Woo (Neurotoxicity Research, 2019)

Bio-solar cell factories for photosynthetic isoprenoids production - Sung Cheon Ko; Hyun Jeong Lee; Sun Young Choi; Jong-il Choi; Han Min Woo (Planta, 2019)

Ursodeoxycholic Acid Inhibits Inflammatory Responses and Promotes Functional Recovery After Spinal Cord Injury in Rats - Wan-Kyu Ko; Seong Jun Kim; Min-Jae Jo; Hyemin Choi; Donghyun Lee; Il Keun Kwon; Soo-Hong Lee; In-Bo Han; Seil Sohn (Molecular Neurobiology, 2019)

Detection of Pathogenic Viruses in the Ambient Air in Seoul, Korea - Tae-Hee Han; Sang-Hun Park; Ju-Young Chung; Hyo-Won Jeong; Jihun Jung; Jae-In Lee; Young-Ok Hwang; Il-Young Kim; Jip-Ho Lee; Kweon Jung (Food and Environmental Virology, 2018)

Erratum to: Loss of Pericytes in Radiation Necrosis after Glioblastoma Treatments - Soon-Tae Lee; Youngbeom Seo; Ji-Yeon Bae; Kon Chu; Jin Wook Kim; Seung Hong Choi; Tae Min Kim; Il Han Kim; Sung-Hye Park; Chul-Kee Park (Molecular Neurobiology, 2018)

Loss of Pericytes in Radiation Necrosis after Glioblastoma Treatments - Soon-Tae Lee; Youngbeom Seo; Ji-Yeon Bae; Kon Chu; Jin Wook Kim; Seung Hong Choi; Tae Min Kim; Il Han Kim; Sung-Hye Park; Chul-Kee Park (Molecular Neurobiology, 2018)

Inhibition of the Voltage-Dependent K+ Current by the Tricyclic Antidepressant Desipramine in Rabbit Coronary Arterial Smooth Muscle Cells - Sung Eun Shin; Hongliang Li; Jin Ryeol An; Mi Seon Seo; Sung Hun Na; Won-Kyo Jung; Amy L. Firth; Kwon-Soo Ha; Eun-Taek Han; Seok-Ho Hong; Il-Whan Choi; Won Sun Park (Cardiovascular Toxicology, 2018)

Plant synthetic GP4 and GP5 proteins from porcine reproductive and respiratory syndrome virus elicit immune responses in pigs - Chul Han An; Salik Nazki; Sung-Chul Park; Yu Jeong Jeong; Ju Huck Lee; Su-Jin Park; Amina Khatun; Won-Il Kim; Youn-Il Park; Jae Cheol Jeong; Cha Young Kim (Planta, 2018)

IDD10 is Involved in the Interaction between NH4+ and Auxin Signaling in Rice Roots - Yuan Hu Xuan; Vikranth Kumar; Xiao Feng Zhu; Byoung Il Je; Chul Min Kim; Jin Huang; Jun Hyeon Cho; Gihwan Yi; Chang-deok Han (Journal of Plant Biology, 2018)

Temperature-dependent immune response of olive flounder (Paralichthys olivaceus) infected with viral hemorrhagic septicemia virus (VHSV) - Jee Youn Hwang; Kesavan Markkandan; Kyudong Han; Mun Gyeong Kwon; Jung Soo Seo; Seung-il Yoo; Seong Don Hwang; Bo Young Ji; Maeng-Hyun Son; Jun-hyung Park (Genes & Genomics, 2018)

A comparison study of the potential risks induced in arable land and forest soils by carcass-derived pollutants - Il Han; Keunje Yoo; Bo Ram Kang; Jee Hyun No; Gui Nam Wee; Muhammad Imran Khan; Tae Young Jeong; Tae Kwon Lee (Environmental Geochemistry and Health, 2018)

Fucoidan inhibits lipopolysaccharide-induced inflammatory responses in RAW 264.7 macrophages and zebrafish larvae - Jin-Woo Jeong; Su Jung Hwang; Min Ho Han; Dae-Sung Lee; Jong Su Yoo; Il-Whan Choi; Hee-Jae Cha; Suhkmann Kim; Heui-Soo Kim; Gi-Young Kim; You-Jin Jeon; Hyo-Jong Lee; et al. (Molecular & Cellular Toxicology, 2017)

Intracellular Remodeling and Accumulation of Aberrant Lysosomes in Differentiation of Tonsil-Derived Mesenchymal Stem Cells into Parathyroid-Like Cells - Young-Il Jo; Gyungah Kim; Yoon Mi Jin; Yoon Jeong Park; Han Su Kim; Yoon Shin Park (Tissue Engineering and Regenerative Medicine, 2017)

Stability Evaluation of National Reference Standards for Blood Products in Korea - Tae Jun Park; Chan Woong Choi; Ho Kyung Oh; Jae Ok Kim; Byung Kuk Kim; Hyun Kyung Kang; Eun Jeong Kwon; Eun Jeong Gweon; Sang Jin Park; Ho Il Kang; Ki Kyung Jung; Sang Mi Park; et al. (Toxicological Research, 2017)

Lipid Emulsion Inhibits Apoptosis Induced by a Toxic Dose of Verapamil via the Delta-Opioid Receptor in H9c2 Rat Cardiomyoblasts - Seong-Ho Ok; Mun Hwan Choi; Il-Woo Shin; Soo Hee Lee; Sebin Kang; Jiah Oh; Jeong Yeol Han; Ju-Tae Sohn (Cardiovascular Toxicology, 2017)

Selective serotonin reuptake inhibitor sertraline inhibits voltage-dependent K+ channels in rabbit coronary arterial smooth muscle cells - Han Sol Kim; Hongliang Li; Hye Won Kim; Sung Eun Shin; Il-Whan Choi; Amy L Firth; Hyoweon Bang; Young Min Bae; Won Sun Park (Journal of Biosciences, 2016)

Policies and Strategies to Overcome Barriers to Rainwater Harvesting for Urban Use in Ethiopia - Tatek Temesgen; Mooyoung Han; Hyunju Park; Tschung-il Kim (Water Resources Management, 2016)

Intranasal Delivery of RGD Motif-Containing Osteopontin Icosamer Confers Neuroprotection in the Postischemic Brain via αvβ3 Integrin Binding - Yin-Chuan Jin; Hahnbie Lee; Seung-Woo Kim; Il-Doo Kim; Hye-Kyung Lee; Yunjin Lee; Pyung-Lim Han; Ja-Kyeong Lee (Molecular Neurobiology, 2016)

Spatial distribution of cold-adapted Synechococcus during spring in seas adjacent to Korea - Dong Han Choi; Jae Hoon Noh; Sung Min An; Yu Ri Choi; Howon Lee; Kongtae Ra; Dongseon Kim; TaeKeun Rho; Sang Heon Lee; Kyung-Tae Kim; Kyung-Il Chang; Jung Ho Lee (Algae, 2016)

The class III anti-arrhythmic agent, amiodarone, inhibits voltage-dependent K+ channels in rabbit coronary arterial smooth muscle cells - Hongliang Li; Han Sol Kim; Hye Won Kim; Sung Eun Shin; Won-Kyo Jung; Kwon-Soo Ha; Eun-Taek Han; Seok-Ho Hong; Amy L. Firth; Young Min Bae; Il-Whan Choi; Won Sun Park (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

An atypical 12q24.31 microdeletion implicates six genes including a histone demethylase KDM2B and a histone methyltransferase SETD1B in syndromic intellectual disability - Jonathan D. J. Labonne; Kang-Han Lee; Shigeki Iwase; Il-Keun Kong; Michael P. Diamond; Lawrence C. Layman; Cheol-Hee Kim; Hyung-Goo Kim (Human Genetics, 2016)

Transgenic Turfgrasses Expressing Hyperactive Ser599Ala Phytochrome A Mutant Exhibit Abiotic Stress Tolerance - Mayank Anand Gururani; Markkandan Ganesan; In-Ja Song; Yunjeong Han; Jeong-Il Kim; Hyo-Yeon Lee; Pill-Soon Song (Journal of Plant Growth Regulation, 2016)

Bacterial biogeography influenced by shelf–basin exchange in the Arctic surface sediment at the C hukchi B orderland - Dukki Han; Seung‐Il Nam; Ho Kyung Ha; Hyoungjun Kim; Michael J. Sadowsky; Yoo Kyung Lee; Hor‐Gil Hur (Environmental Microbiology, 2016)
Summary It has been known that continental shelves around the A rctic O cean play a major role in the ventilation of the deep basins as a consequence of shelf–basin exchange. In the present study, we found that bacterial assemblage of the surface sediment was different from that of seawater while seawater harboured local bacterial assemblages in response to the A rctic hydrography. This finding suggests that the Arctic seafloor sediments may have distinctive bacterial biogeography. Moreover, the distribution of bacterial assemblages and physicochemical properties in surface sediments changed gradually from the A rctic continental shelf to deep‐sea basin. Based on the results, bacterial biogeography in the A rctic seafloor sediments may be influenced by winnowing and re‐deposition of surface sediments through the sediment gravity flow. The present study offers a deeper understanding of shelf convection and its role for the construction of bacterial assemblages in the A rctic O cean.

Prokaryotic community composition revealed by denaturing gradient gel electrophoresis in the East Sea - Gwang Il Jang; Dong Han Choi (Ocean Science Journal, 2015)

A novel synthetic chalcone derivative promotes caspase-dependent apoptosis through ROS generation and activation of the UPR in MH7A cells - Jin-Hyun Kim; Yong-Joon Jeon; Jaewook Cho; Jong-Il Shin; Chae Yun Baek; Yoongho Lim; Dongsoo Koh; Soon Young Shin; Young Han Lee; Kyungho Lee (Genes & Genomics, 2015)

Statistical modeling for selecting a superior working dog using microsatellite loci - Hoim Jeong; Kyeongjun Lee; Bong-Hwan Choi; Hee-Eun Lee; Jeong-An Gim; Dong-Hoon Lee; Ji-Hong Ha; Kook-Il Han; Youngseuk Cho; Heui-Soo Kim (Genes & Genomics, 2015)

Size-dependent clearance of gold nanoparticles from lungs of Sprague–Dawley rats after short-term inhalation exposure - Sung Gu Han; Jong Seong Lee; Kangho Ahn; Yong Soon Kim; Jin Kwon Kim; Ji Huyn Lee; Jae Hoon Shin; Ki Soo Jeon; Wan Seob Cho; Nam Woong Song; Mary Gulumian; Beom Soo Shin; et al. (Archives of Toxicology, 2015)

Glycan structure and serum half-life of recombinant CTLA4Ig, an immunosuppressive agent, expressed in suspension-cultured rice cells with coexpression of human β1,4-galactosyltransferase and human CTLA4Ig - Seung Hoon Kang; Hahn Sun Jung; Song Jae Lee; Cheon Ik Park; Sang Min Lim; Heajin Park; Byung Sun Kim; Kwang Heum Na; Gyeong Jin Han; Jae Woo Bae; Hyun Joo Park; Keuk Chan Bang; et al. (Glycoconjugate Journal, 2015)

Construction of target‐specific virus‐like particles for the delivery of algicidal compounds to harmful algae - Beom Sik Kang; Chi‐Yong Eom; Wonduck Kim; Pyoung il Kim; Sun Yi Ju; Jaewon Ryu; Gui Hwan Han; Jeong‐Il Oh; Hoon Cho; Seung Ho Baek; Gueeda Kim; Minju Kim; et al. (Environmental Microbiology, 2015)
Summary Harmful algal blooms ( HABs ) can lead to substantial socio‐economic losses and extensive damage to aquatic ecosystems, drinking water sources and human health. Common algicidal techniques, including ozonation, ultrasonic treatment and dispersion of algae‐killing chemicals, are unsatisfactory both economically and ecologically. This study therefore presents a novel alternative strategy for the efficient control of deleterious algae via the use of host‐specific virus‐like particles ( VLPs ) combined with chemically synthesized algicidal compounds. The capsid protein of HcRNAV34 , a single‐stranded RNA virus that infects the toxic dinoflagellate, H eterocapsa circularisquama , was expressed in and purified from E scherichia coli and then self‐assembled into VLPs in vitro . Next, the algicidal compound, thiazolidinedione 49 ( TD49 ), was encapsidated into HcRNAV34 VLPs for specific delivery to H . circularisquama . Consequently, HcRNAV34 VLPs demonstrated the same host selectivity as naturally occurring HcRNAV34 virions, while TD49 ‐encapsidated VLPs showed a more potent target‐specific algicidal effect than TD49 alone. These results indicate that target‐specific VLPs for the delivery of cytotoxic compounds to nuisance algae might provide a safe, environmentally friendly approach for the management of HABs in aquatic ecosystems.

Salinity-dependent changes in growth and fatty acid composition of new Arctic Chlamydomonas species, ArM0029A - Joon-Woo Ahn; Kwon Hwangbo; Chun Ji Yin; Jong-Min Lim; Han-Gu Choi; Youn-Il Park; Won-Joong Jeong (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Polymorphism analysis of tyrosine hydroxylase gene variable number of tandem repeats in various Korean dogs - Hee-Eun Lee; Bong-Hwan Choi; Dong-Hoon Lee; Yun-Jeong Kwon; Jungwoo Eo; Yuri Choi; Hoim Jeong; Jeong-An Gim; Tae-Hun Kim; Ji-Hong Ha; Kook-Il Han; Heui-Soo Kim (Genes & Genomics, 2015)

Characterization of a small constitutive promoter from Arabidopsis translationally controlled tumor protein (AtTCTP) gene for plant transformation - Yun-Jeong Han; Yong-Min Kim; Ok-Jin Hwang; Jeong-Il Kim (Plant Cell Reports, 2015)

Characterization and chemical control of soft rot disease caused by Pantoea sp. strain PPE7 in Pleurotus eryngii mushroom crops - Min Keun Kim; Song Hee Lee; Young Han Lee; HyeRan Kim; JeongYeo Lee; Il Rae Rho (European Journal of Plant Pathology, 2015)

Cellular localization and detergent dependent oligomerization of rice allene oxide synthase-1 - Sereyvath Yoeun; Jeong-Il Kim; Oksoo Han (Journal of Plant Research, 2015)

The effect of composite graft with deproteinized bovine bone mineral and mineralized solvent-dehydrated bone on exophytic bone formation in rabbit calvarial model - Hwa-Suk Seok; Yeek Herr; Jong-Hyuk Chung; Seung-Il Shin; Ji-Young Han; Seung-Yun Shin (Tissue Engineering and Regenerative Medicine, 2014)

Soil insect pests of cold temperate zones of East Asia, including DPR Korea: A review - Stefan Toepfer; Hongmei Li; Song Gun Pak; Kyong Man Son; Yong Suk Ryang; Song Il Kang; Richou Han; Keith Holmes (Journal of Pest Science, 2014)

Statistical analysis and genetic diversity of three dog breeds using simple sequence repeats - Hoim Jeong; Bong-Hwan Choi; Jungwoo Eo; Yun-Jeong Kwon; Hee-Eun Lee; Yuri Choi; Jeong-An Gim; Tae-Hun Kim; Hwan-Hoo Seong; Dong-Hoon Lee; Ji-Hong Ha; Kook-Il Han; et al. (Genes & Genomics, 2014)

Analysis of Fish DNA Biomarkers as a Molecular-Level Approach for Ecological Health Assessments in an Urban Stream - Nami Kang; Han-il Kang; Kwang-Guk An (Bulletin of Environmental Contamination and Toxicology, 2014)

Integrative assessment of sediment quality in terms of chemical contamination in Jinhae Bay, South Korea - Sang Hee Hong; Gi Myung Han; Un Hyuk Yim; Dhong-il Lim; Sung Yong Ha; Nam Sook Kim; Won Joon Shim (Ocean Science Journal, 2014)

Spirosoma radiotolerans sp. nov., a Gamma-Radiation-Resistant Bacterium Isolated from Gamma Ray-Irradiated Soil - Jae-Jin Lee; Sathiyaraj Srinivasan; Sangyong Lim; Minho Joe; Seonghun Im; So Il Bae; Kyoung Ryun Park; Ji-Hee Han; Se-Hee Park; Bo-min Joo; Sol-Ji Park; Myung Kyum Kim (Current Microbiology, 2014)

Human hair keratin and its-based biomaterials for biomedical applications - Hanna Lee; Kwantae Noh; Sang Cheon Lee; Il-Keun Kwon; Dong-Wook Han; In-Seop Lee; Yu-Shik Hwang (Tissue Engineering and Regenerative Medicine, 2014)

Over-expression of PsGPD, a mushroom glyceraldehyde-3-phosphate dehydrogenase gene, enhances salt tolerance in rice plants - Jung-Il Cho; Hye-Min Lim; Zamin Shaheed Siddiqui; Sung-Han Park; A-Ram Kim; Taek-Ryoun Kwon; Seong-Kon Lee; Soo-Chul Park; Mi-Jeong Jeong; Gang-Seob Lee (Biotechnology Letters, 2014)

ENA-A actimineral resource A extends lifespan associated with antioxidant mechanism in SMP30 knockout mice - Jung-Youn Han; Meeyul Hwang; Sung-Yong Hwa; Jin-Kyu Park; Mi-Ran Ki; Il-Hwa Hong; Ah-Young Kim; Eun-Mi Lee; Eun-Joo Lee; Chang-Woo Min; Kyung-Ku Kang; Myeong-Mi Lee; et al. (Molecular and Cellular Biochemistry, 2014)

Expression analysis of transcripts responsive to osmotic stress in Deschampsia antarctica Desv. - Jungeun Lee; Hyoungseok Lee; Eun Kyeung Noh; Mira Park; Hyun Park; Ji Hyun Kim; Il-Chan Kim; Joung Han Yim (Genes & Genomics, 2014)

Chitosan-Based Polyelectrolyte Complexes as Potential Nanoparticulate Carriers: Physicochemical and Biological Characterization - Thiruganesh Ramasamy; Tuan Hiep Tran; Hyuk Jun Cho; Jeong Hwan Kim; Yong Il Kim; Jae Yoon Jeon; Han-Gon Choi; Chul Soon Yong; Jong Oh Kim (Pharmaceutical Research, 2014)

Physiological mechanism of drought tolerance in transgenic rice plants expressing Capsicum annuum methionine sulfoxide reductase B2 (CaMsrB2) gene - Zamin Shaheed Siddiqui; Jung-Il Cho; Taek-Ryoun Kwon; Byung-Ok Ahn; Kang-Seob Lee; Mi-Jeong Jeong; Tae-Hun Ryu; Seong-Kon Lee; Soo-Chul Park; Sung-Han Park (Acta Physiologiae Plantarum, 2014)

Agrobacterium-mediated genetic transformation of Miscanthus sinensis - Ok-Jin Hwang; Mi-Ae Cho; Yun-Jeong Han; Yong-Min Kim; Soo-Hyun Lim; Do-Soon Kim; Ildoo Hwang; Jeong-Il Kim (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Prognosis of hepatocellular carcinoma patients with extrahepatic metastasis and the controllability of intrahepatic lesions - Jung Il Lee; Ja Kyung Kim; Do Young Kim; Sang Hoon Ahn; Jun Yong Park; Seung Up Kim; Beom Kyung Kim; Kwang Hyub Han; Kwan Sik Lee (Clinical & Experimental Metastasis, 2014)

A new approach for discovering cold-active enzymes in a cell mixture of pure-cultured bacteria - Dockyu Kim; Ha Ju Park; Il-Chan Kim; Joung Han Yim (Biotechnology Letters, 2014)

Combined effects of an antioxidant and caspase inhibitor on the reversal of hepatic fibrosis in rats - Do Young Kim; Sook In Chung; Simon Weonsang Ro; Yong Han Paik; Jung Il Lee; Man Kil Jung; Min Goo Lee; Young Nyun Park; Kwan Sik Lee; Jung Gyu Park; Hee Dong Park; Kwang-Hyub Han (Apoptosis, 2013)

Fertilizer N uptake of paddy rice in two soils with different fertility under experimental warming with elevated CO2 - Hong-Shik Nam; Jin-Hyeob Kwak; Sang-Sun Lim; Woo-Jung Choi; Sun-Il Lee; Dong-Suk Lee; Kwang-Seung Lee; Han-Yong Kim; Sang-Mo Lee; Miwa Matsushima (Plant and Soil, 2013)

A1E inhibits proliferation and induces apoptosis in NCI-H460 lung cancer cells via extrinsic and intrinsic pathways - Yesol Bak; Sunyoung Ham; O. Baatartsogt; Seung hyun Jung; Kang-Duk Choi; Tae-Young Han; Il-Young Han; Do-Young Yoon (Molecular Biology Reports, 2013)

OsSNDP1, a Sec14-nodulin domain-containing protein, plays a critical role in root hair elongation in rice - Jin Huang; Chul Min Kim; Yuan-hu Xuan; Soon Ju Park; Hai Long Piao; Byoung Il Je; Jingmiao Liu; Tae Ho Kim; Bo-Kyeong Kim; Chang-Deok Han (Plant Molecular Biology, 2013)

Elimination of Chrysanthemum stunt viroid (CSVd) from meristem tip culture combined with prolonged cold treatment - Wina Dian Savitri; Kyung Il Park; Su Min Jeon; Mi Young Chung; Jeung-Sul Han; Chang Kil Kim (Horticulture, Environment, and Biotechnology, 2013)

Overexpression of Arabidopsis ABF3 gene confers enhanced tolerance to drought and heat stress in creeping bentgrass - Yun-Sung Choi; Yong-Min Kim; Ok-Jin Hwang; Yun-Jeong Han; Soo Young Kim; Jeong-Il Kim (Plant Biotechnology Reports, 2013)

Analysis of mRNA expression profiles highlights alterations in modulation of the DNA damage-related genes under butanal exposure in A549 human alveolar epithelial cells - Hyo-Sun Lee; Mi-Kyung Song; Han-Seam Choi; Chan-Young Shin; Eun-Il Lee; Jae-Chun Ryu (Molecular & Cellular Toxicology, 2013)

Analysis of histone deacetylase inhibitor-induced responses in human periodontal ligament fibroblasts - Tae-Il Kim; Ji-Eun Han; Hong-Moon Jung; Joung-Hwan Oh; Kyung Mi Woo (Biotechnology Letters, 2013)

Constitutive activation of brassinosteroid signaling in the Arabidopsis elongated-D/bak1 mutant - Yuhee Chung; Vitnary Choe; Shozo Fujioka; Suguru Takatsuto; Muho Han; Jong-Seong Jeon; Youn-Il Park; Kyun Oh Lee; Sunghwa Choe (Plant Molecular Biology, 2012)

Erratum to: Overexpression of phytochrome A and its hyperactive mutant improves shade tolerance and turf quality in creeping bentgrass and zoysiagrass - Markkandan Ganesan; Yun-Jeong Han; Tae-Woong Bae; Ok-Jin Hwang; Thummala Chandrasekhar; Ah-Young Shin; Chang-Hyo Goh; Satoshi Nishiguchi; In-Ja Song; Hyo-Yeon Lee; Jeong-Il Kim; Pill-Soon Song (Planta, 2012)

Overexpression of phytochrome A and its hyperactive mutant improves shade tolerance and turf quality in creeping bentgrass and zoysiagrass - Markkandan Ganesan; Yun-Jeong Han; Tae-Woong Bae; Ok-Jin Hwang; Thummala Chandrasekkhar; Ah-Young Shin; Chang-Hyo Goh; Satoshi Nishiguchi; In-Ja Song; Hyo-Yeon Lee; Jeong-Il Kim; Pill-Soon Song (Planta, 2012)

Overexpression of an Arabidopsis β-glucosidase gene enhances drought resistance with dwarf phenotype in creeping bentgrass - Yun-Jeong Han; Kyu-Chang Cho; Ok-Jin Hwang; Yun-Sung Choi; Ah-Young Shin; Inhwan Hwang; Jeong-Il Kim (Plant Cell Reports, 2012)

Synthesis and evaluation of thiopyrano[3,4-c]quinoline-9-carboxamide derivatives as inhibitors of poly(ADP-ribose) polymerase-1 (PARP-1) - Chun-Ho Park; Kwangwoo Chun; Bo-Young Joe; Jong-Hee Choi; Han-Chang Lee; Il-Whea Ku; Hyun Young Kim; Seong-Ho Koh; Goang Won Cho; Seung Hyun Kim; Myung-Hwa Kim (Medicinal Chemistry Research, 2012)

The global temperature anomaly and solar North-South asymmetry - Il-Hyun Cho; Young-Sil Kwak; Heon-Young Chang; Kyung-Suk Cho; Yeon-Han Kim; Young-Deuk Park (Asia-Pacific Journal of Atmospheric Sciences, 2012)

OsREL2, a rice TOPLESS homolog functions in axillary meristem development in rice inflorescence - Yerim Kwon; Si-in Yu; Joo-hyuk Park; Ying Li; Jin-Hee Han; Hemasundar Alavilli; Jung-Il Cho; Tae-Houn Kim; Jong-Seong Jeon; Byeong-ha Lee (Plant Biotechnology Reports, 2012)

Species relationships among Allium species by ISSR analysis - Jae-Han Son; Kyong-Cheul Park; Sung-Il Lee; Jong-Hwa Kim; Nam-Soo Kim (Horticulture, Environment, and Biotechnology, 2012)

Prevalence and genetic characterization of respiratory syncytial virus (RSV) in hospitalized children in Korea - Yun Hee Baek; Eun Hye Choi; Min-Suk Song; Philippe Noriel Q. Pascua; Hyeok-il Kwon; Su-Jin Park; Jun Han Lee; Sung-Il Woo; Byung-Hoon Ahn; Heon-Seok Han; Yoon-Soo Hahn; Kyeong-Seob Shin; et al. (Archives of Virology, 2012)

Ascochlorin suppresses TGF-β1-induced PAI-1 expression through the inhibition of phospho-EGFR in rat kidney fibroblast cells - Hyun-Ji Cho; Jeong-Han Kang; Ji-Hak Jeong; Yun-Jeong Jeong; Kwan-Kyu Park; Yoon-Yub Park; Yong-Suk Moon; Hong-Tae Kim; Il-Kyung Chung; Cheorl-Ho Kim; Hyeun-Wook Chang; Young-Chae Chang (Molecular Biology Reports, 2012)

Impact of body mass index in Korean patients with renal cell carcinoma - Hyun Hwan Sung; Seong Soo Jeon; Seo Yong Park; Byong Chang Jeong; Seong Il Seo; Hyun Moo Lee; Han-Yong Choi (Cancer Causes & Control, 2012)

Sequence Variation and Comparison of the 5S rRNA Sequences in Allium Species and their Chromosomal Distribution in Four Allium Species - Jae-Han Son; Kyong-Cheul Park; Sung-Il Lee; Eun-Jin Jeon; Hyun-Hee Kim; Nam-Soo Kim (Journal of Plant Biology, 2012)

Isolation of cold-responsive genes from garlic, Allium sativum - Jae-Han Son; Kyong-Cheul Park; Sung-Il Lee; Haeng-Hoon Kim; Jong-Hwa Kim; Sun-Hyung Kim; Nam-Soo Kim (Genes & Genomics, 2012)

The Protective Effect of ENA Actimineral Resource A on CCl4-Induced Liver Injury in Rats - Il-Hwa Hong; Hoon Ji; Sung-Yong Hwa; Won-Il Jeong; Da-Hee Jeong; Sun-Hee Do; Ji-Min Kim; Mi-Ran Ki; Jin-Kyu Park; Moon-Jung Goo; Ok-Kyung Hwang; Kyung-Sook Hong; et al. (Marine Biotechnology, 2011)

Assessment of change in design flood frequency under climate change using a multivariate downscaling model and a precipitation-runoff model - Hyun-Han Kwon; Bellie Sivakumar; Young-Il Moon; Byung-Sik Kim (Stochastic Environmental Research and Risk Assessment, 2011)

Identification of S-allele genotypes of Korean apple cultivars by using allele-specific polymerase chain reaction - Seong Heo; Sang Eun Han; Soon Il Kwon; Ji Hae Jun; Mok Jong Kim; Hee Jae Lee (Horticulture, Environment, and Biotechnology, 2011)

Titanium dioxide inclusion in backing reduce the photoallergenicity of ketoprofen transdermal patch - Yang-Gyu Choi; Ji Hae Lee; Il-Hong Bae; Young-Chang Ah; Han-Moe Ki; Jun-Ho Bae; Young-Ho Park; Kang Choon Lee; Kyung-Min Lim (Archives of Toxicology, 2011)

Dissolved organic phosphorus utilization and alkaline phosphatase activity of the dinoflagellate Gymnodinium impudicum isolated from the South Sea of Korea - Seok Jin Oh; Hyeong Kyu Kwon; Il Hyeon Noh; Han-Soeb Yang (Ocean Science Journal, 2010)

Gentamicin-Loaded Wound Dressing With Polyvinyl Alcohol/Dextran Hydrogel: Gel Characterization and In Vivo Healing Evaluation - Ma-Ro Hwang; Jong Oh Kim; Jeong Hoon Lee; Yong Il Kim; Jeong Hoon Kim; Sun Woo Chang; Sung Gju Jin; Jung Ae Kim; Won Seok Lyoo; Sung Soo Han; Sae Kwang Ku; Chul Soon Yong; et al. (AAPS PharmSciTech, 2010)

c-myb has a character of oxidative stress resistance in aged human diploid fibroblasts: regulates SAPK/JNK and Hsp60 pathway consequently - Young-Hee Lee; Nan-Hee Lee; Govinda Bhattarai; Pyong-Han Hwang; Tae-Il Kim; Eun-Chung Jhee; Ho-Keun Yi (Biogerontology, 2010)

Complementary DNA library construction and expressed sequence tag analysis of an Arctic moss, Aulacomnium turgidum - Shenghao Liu; Hyoungseok Lee; Pil-Sung Kang; Xiaohang Huang; Joung Han Yim; Hong Kum Lee; Il-Chan Kim (Polar Biology, 2010)

Rapid detection of virulence stx2 gene of Enterohemorrhagic Escherichia coli using two-step ultra-rapid real-time PCR - Il-Wook Kim; Min-Hee Kang; Soon-Hwan Kwon; Seung-Hak Cho; Byung-Sun Yoo; Sang-Hoon Han; Byoung-Su Yoon (Biotechnology Letters, 2010)

Human dermal fibroblast proliferation activity of usimine-C from Antarctic lichen Ramalina terebrata - Sung Gu Lee; Hye Yeon Koh; Hyuncheol Oh; Se Jong Han; Il-Chan Kim; Hong Kum Lee; Joung Han Yim (Biotechnology Letters, 2010)

1D crustal velocity structure beneath broadband seismic stations in the Okcheon Fold Belt of Korea by receiver function analysis - Sung Il Han; Jung Mo Lee; Tae-Seob Kang (Geosciences Journal, 2010)

Gene expression profiling in the lung tissue of cynomolgus monkeys in response to repeated exposure to welding fumes - Jeong-Doo Heo; Jung-Hwa Oh; Kyuhong Lee; Choong Yong Kim; Chang-Woo Song; Seokjoo Yoon; Jin Soo Han; Il Je Yu (Archives of Toxicology, 2010)

Hypothyroidism Induced by Polychlorinated Biphenyls and Up-Regulation of Transthyretin - Dae-Yong Han; Sang-Rim Kang; Oh-Sung Park; Jae-Hyeon Cho; Chung-Kil Won; Hyeon-Soo Park; Kwang-Il Park; Eun-Hee Kim; Gon-Sup Kim (Bulletin of Environmental Contamination and Toxicology, 2010)

Effects of Repeated Seafood Consumption on Urinary Excretion of Arsenic Species by Volunteers - Byung-Sun Choi; Seong-Jin Choi; Dong-Won Kim; Mingai Huang; Na-Young Kim; Kyung-Su Park; Choong-Yong Kim; Hyo-Min Lee; Young-Na Yum; Eui-Sik Han; Tae-Seok Kang; Il-Je Yu; et al. (Archives of Environmental Contamination and Toxicology, 2010)

The complete mitogenome sequence of the Japanese oak silkmoth, Antheraea yamamai (Lepidoptera: Saturniidae) - Seong Ryeol Kim; Man Il Kim; Mee Yeon Hong; Kee Young Kim; Pil Don Kang; Jae Sam Hwang; Yeon Soo Han; Byung Rae Jin; Iksoo Kim (Molecular Biology Reports, 2009)

Analysis of genetic diversity and population structure of rice cultivars from Korea, China and Japan using SSR markers - Weiguo Zhao; Jong-Wook Chung; Kyung-Ho Ma; Tae-San Kim; Seung-Min Kim; Dong-Il Shin; Chang-Ho Kim; Han-Mo Koo; Yong-Jin Park (Genes & Genomics, 2009)

Benzene activates caspase-4 and -12 at the transcription level, without an association with apoptosis, in mouse bone marrow cells lacking the p53 gene - Jung-Yeon Yi; Yoko Hirabayashi; Yang-Kyu Choi; Yukio Kodama; Jun Kanno; Jeong-Hee Han; Tohru Inoue; Byung-Il Yoon (Archives of Toxicology, 2009)

Relating Tree Ring Chemistry of Pinus densiflora to Precipitation Acidity in an Industrial Area of South Korea - Jin-Hyeob Kwak; Sang-Sun Lim; Hyun-Jung Park; Sun-Il Lee; Kye-Han Lee; Han-Yong Kim; Scott X. Chang; Sang-Mo Lee; Hee-Myong Ro; Woo-Jung Choi (Water, Air, & Soil Pollution, 2009)

Proteomic analysis of rice mutants susceptible to Magnaporthe oryzae - Hak-Seung Ryu; Min-Young Song; Chi-Yeol Kim; Muho Han; Sang-Kyu Lee; Nayeon Ryoo; Jung-Il Cho; Tae-Ryong Hahn; Jong-Seong Jeon (Plant Biotechnology Reports, 2009)

Production of purple-colored creeping bentgrass using maize transcription factor genes Pl and Lc through Agrobacterium-mediated transformation - Yun-Jeong Han; Yong-Min Kim; Jee-Yeon Lee; Soo Jung Kim; Kyu-Chang Cho; Thummala Chandrasekhar; Pill-Soon Song; Young-Min Woo; Jeong-Il Kim (Plant Cell Reports, 2009)

Temporal Variations in Seaweed Biomass in Korean Coasts: Woejodo and Jusamdo, Jeonbuk - Han-Gil Choi; Ki-Hun Lee; Xiao Qin Wan; Hyun-Il Yoo; Hyang-Ha Park; Jeong-Ha Kim; Ik-Kyo Chung (Algae, 2008)

Physiological differences in the growth of Sargassum horneri between the germling and adult stages - Han Gil Choi; Ki Hoon Lee; Hyun Il Yoo; Pil Jun Kang; Young Sik Kim; Ki Wan Nam (Journal of Applied Phycology, 2008)

Essais d’altération chimique accélérée au laboratoire par le double extracteur Soxhlet. Application à des roches granitiques de Corée du Sud - Ik Woo; Jean-Alain Fleurisson; Yoen-Jun Park; Kong-Chang Han; Won-Kyung Song; Hyuck-Jin Park; Il-Soo Kim (Bulletin of Engineering Geology and the Environment, 2008)

Effects of irradiance of various wavelengths from light-emitting diodes on the growth of the harmful dinoflagellate Heterocapsa circularisquama and the diatom Skeletonema costatum - Seok Jin OH; Dae-Il KIM; Takao SAJIMA; Yohei SHIMASAKI; Yukihiko MATSUYAMA; Yuji OSHIMA; Tsuneo HONJO; Han-Soeb YANG (Fisheries Science, 2008)

A Ds-insertion mutant of OSH6 (Oryza sativa Homeobox 6) exhibits outgrowth of vestigial leaf-like structures, bracts, in rice - Sung Han Park; Chul Min Kim; Byoung Il Je; Su Hyun Park; Soon Ju Park; Hai Long Piao; Yuan-hu Xuan; Mi Sook Choe; Kouji Satoh; Shoshi Kikuchi; Kon Ho Lee; Young Soon Cha; et al. (Planta, 2007)

Analysis of gene-trap Ds rice populations in Korea - Sung Han Park; Nam Soo Jun; Chul Min Kim; Tae Yong Oh; Jin Huang; Yuan-hu Xuan; Soon Ju Park; Byoung Il Je; Hai Long Piao; Soo Hyun Park; Young Soon Cha; Byung Ohg Ahn; et al. (Plant Molecular Biology, 2007)

Seasonal Community Structure and Vertical Distribution of Medicinal Seaweeds at Kkotji in Taean Peninsula, Korea - Ki-Hun Lee; Hyun-Il Yoo; Han-Gil Choi (Algae, 2007)

Growth and tuberization of transgenic potato plants expressing sense and antisense sequences of Cu/Zn superoxide dismutase from lily chloroplasts - Mi Sun Kim; Hyun Soon Kim; Han Na Kim; Yoon Shik Kim; Kwang Hyun Baek; Youn Il Park; Hyouk Joung; Jae Heung Jeon (Journal of Plant Biology, 2007)

Microarray analysis of apple gene expression engaged in early fruit development - Young-Pyo Lee; Gyung-Hee Yu; Young Sam Seo; Sang Eun Han; Yeon-Ok Choi; Daeil Kim; Il-Gin Mok; Woo Taek Kim; Soon-Kee Sung (Plant Cell Reports, 2007)

OECD validation of the rodent Hershberger assay using three reference chemicals; 17α-methyltestosterone, procymidone, and p,p′-DDE - Jae-Ho Shin; Hyun Ju Moon; Il Hyun Kang; Tae Sung Kim; Su Jung Lee; Ji Youn Ahn; Hoon Bae; Eui Bae Jeung; Soon Young Han (Archives of Toxicology, 2007)

A peroxisome-proliferator activated receptor-γ ligand could regulate the expression of leptin receptor on human hepatic stellate cells - Jung Il Lee; Yong-Han Paik; Kwan Sik Lee; Jin Woo Lee; Yong Soo Kim; Seok Jeong; Kye Sook Kwon; Dong Haeng Lee; Hyung Gil Kim; Yong Woon Shin; Min Ah Kim (Histochemistry and Cell Biology, 2007)

Repeated 28-day oral toxicity study of ketoconazole in rats based on the draft protocol for the “Enhanced OECD Test Guideline No. 407” to detect endocrine effects - Jae-Ho Shin; Hyun Ju Moon; Il Hyun Kang; Tae Sung Kim; In Young Kim; In Sook Park; Hyung Sik Kim; Eui Bae Jeung; Soon-Young Han (Archives of Toxicology, 2006)

Repeated 28-day oral toxicity study of vinclozolin in rats based on the draft protocol for the “Enhanced OECD Test Guideline No. 407” to detect endocrine effects - Jae-Ho Shin; Hyun Ju Moon; Tae Sung Kim; Il Hyun Kang; Ho Yeon Ki; Kwang Sik Choi; Soon Young Han (Archives of Toxicology, 2006)

A comprehensive expression analysis of the WRKY gene superfamily in rice plants during defense response - Hak-Seung Ryu; Muho Han; Sang-Kyu Lee; Jung-Il Cho; Nayeon Ryoo; Sunggi Heu; Youn-Hyung Lee; Seong Hee Bhoo; Guo-Liang Wang; Tae-Ryong Hahn; Jong-Seong Jeon (Plant Cell Reports, 2006)

Improvement of overtopping risk evaluations using probabilistic concepts for existing dams - Hyun-Han Kwon; Young-Il Moon (Stochastic Environmental Research and Risk Assessment, 2006)

Studies on the mobilization of a maize transposable family,Ac/Ds, in pepper using In Vivo transient assay system - Chul Min Kim; Byoung Il Je; Ja Choon Koo; Hai Long Piao; Soon Ju Park; Joo Mi Jeon; Min Kyoung Kim; Sung Han Park; Jin Young Park; Eun Jin Lee; Woo Sik Chung; Kon Ho Lee; et al. (Journal of Plant Biology, 2004)

Electroosmosis and pore pressure development characteristics in lead contaminated soil during electrokinetic remediation - Sang-Jae Han; Soo-Sam Kim; Byung-Il Kim (Geosciences Journal, 2004)

Optimization of Bifidobacterium longum growth by use of calcium carbonate-alginate beads - Su-Han Song; Teak-Bum Kim; Hoon-Il Oh; Deok-Kun Oh (World Journal of Microbiology and Biotechnology, 2003)

Design and biological activity of synthetic oligopeptides with Pro-His-Ser-Arg-Asn (PHSRN) and Arg-Gly-Asp (RGD) motifs for human osteoblast-like cell (MG-63) adhesion - Tae-Il Kim; Jun-Hyeog Jang; Yong-Moo Lee; In-Cheol Ryu; Chong-Pyoung Chung; Soo-Boo Han; Sang-Mook Choi; Young Ku (Biotechnology Letters, 2002)

Stereochemical control in diastereoselective reduction of α-substituted-β-ketoesters using a reductase purified from Kluyveromyces marxianus - Joo Hwan Cha; Ae Nim Pae; Kyung Il Choi; Yong Seo Cho; Wook Hyun Kim; Ye Sun Han; Hong-Chul Yun; Jongsoo Lee; Hun Yeong Koh; Eun Lee (Biotechnology Letters, 2002)

Intramitochondrial pyruvate attenuates hydrogen peroxide-induced apoptosis in bovine pulmonary artery endothelium - Young-Hee Kang; Se-Jin Chung; Il-Jun Kang; Jung Han Yoon Park; Rolf Bunger (Molecular and Cellular Biochemistry, 2001)

Effect of polyamines on adventitious root formation from Tobacco (Nicotiana tabaccum) leaf segments - Myoung-Goo Jeon; Hyeong-il Jo; Tae-Jin Han (Journal of Plant Biology, 1998)